Medicinal and Phytochemical Profiling of Aegle marmelos - Brij Bhushan Tewari; Subramanian Gomatinayagam; Ashish Kumar Tiwari (Contemporary Research and Perspectives in Biological Science Vol. 8, 2025)
Aegle marmelos (L) is native to the Indian subcontinent and Southeast Asia and well known for its therapeutic values such as anti-diabetic activity, hepatoprotective activities, antimicrobial activity, analgesic anti-inflammatory, antifungal activity, anticancer activity, antiulcer activity, antithyroid activity, etc. Present studies report phytochemical analysis, and antifungal antibacterial screening of acetone, ethanol and methanol leaf extract of Aegle marmelos. The plant material leaves of Aegle marmelos were collected from Cove and John Ashram, Georgetown, Guyana. Leaves are dried in the oven at 50-55 ºC for 72 h. The moisture content is calculated. The dried leaves were ground and extracted in each acetone, ethanol and methanol solvent. Extracts were collected and evaporation of solvent was done on rotavapour. The antimicrobial and antifungal activity of leaf extract was examined by well diffusion, poison plate, paper disc plate and streak plate methods. Three micro-organisms (Escherichia coli, Staphylococcus aureus and Candidus albicans) were used for the study as test organisms. In Aegle marmelos leaf extract studies, maximum and minimum antimicrobial potential was observed for methanol and acetone solvents, respectively. The antimicrobial potential of leave extract was also found to be maximum and minimum in Candida albicans and Escherichia coli, respectively in most assay studies. The maximum inhibitory zone for methanolic leaves extract of Aegle marmelos were observed to be (125 µL: 0.47mm), (125 µL: 0.51 mm), (125 µL: 0. 47mm) and (125 µL: 0.37 mm) by well diffusion, poison plate, paper disc plate and streak plate methods respectively. The phyto constituents, tannins, flavonoids, alkaloids, terpenoids, phenol, steroids and Phyto steroids were found to be present in the methanol leave extract of Aegle marmelos. It is concluded that Aegle marmelos extracts can be used for the treatment of tuberculosis, urinary disease, diabetes, digestive disorder, epilepsy, ulcers etc.